The Potential of Different Origin Stem Cells in Modulating Oral Bone Regeneration Processes - Smaranda Dana Buduru; Diana Gulei; Alina-Andreea Zimta; Adrian Bogdan Tigu; Diana Cenariu; Ioana Berindan-Neagoe (Cells, 2019)
Tissue engineering has gained much momentum since the implementation of stem cell isolation and manipulation for regenerative purposes. Despite significant technical improvements, researchers still have to decide which strategy (which type of stem cell) is the most suitable for their specific purpose. Therefore, this short review discusses the advantages and disadvantages of the three main categories of stem cells: embryonic stem cells, mesenchymal stem cells and induced pluripotent stem cells in the context of bone regeneration for dentistry-associated conditions. Importantly, when deciding upon the right strategy, the selection needs to be made in concordance with the morbidity and the life-threatening level of the condition in discussion. Therefore, even when a specific type of stem cell holds several advantages over others, their availability, invasiveness of the collection method and ethical standards become deciding parameters.